Roadmappingsystem for knowledge generation, storage, and sharing - Yee, Choy Leong (Universiti Utara Malaysia, 2012)
This paper describes a road mapping system for knowledge generation, storage, and sharing. It illustrates the theory and practice of road mapping. How the system is being used is also presented in a step-by-step format. The paper ends with discussing the process of generation, storage, and sharing of knowledge.